Set-jetting jako przykład praktykowania krajobrazu filmowego - Copik, Ilona (Przestrzenie Teorii, 2025)
The assumption adopted in the article is the ambiguous status of the film landscape and its borderline identity, which results from its location ‘between’ the screen (the image) and the film set (the real place/environment). This understanding of the landscape confirms and at the same time reinforces the contemporary phenomenon of set-jetting, a phenomenon defined as the tendency to visit locations known from different films and series. This study seeks to answer the questions: What is set-jetting as a cultural practice? In what sense is it a new version of well-known cultural tourism, and in what sense is it a typical product of consumer culture, part of a networked circulation of images? How does set-jetting affect real places and local communities? What are contemporary tourist sites, how much fiction and how much reality are in them, to what extent do they contain an authentic story about a place, and to what extent secondary, individualised fabulations. The final aim of the discussion is an attempt to identify the types of landscape practice by contemporary viewers/tourists.